Comparison of chest- and wrist-based actigraphy in pulmonary arterial hypertension. Issue 1 (2nd November 2021) - Lachant, Daniel; Light, Allison; Hannon, Kevin; Abbas, Farrukh; Lachant, Michael; White, R James
Abstract: Aims: Activity trackers for clinical trials and remote monitoring are appealing as they provide objective data outside of the clinic setting. Algorithms determine physical activity intensity and count steps. Multiple studies show physical inactivity in pulmonary arterial hypertension (PAH). There are no studies comparing different activity trackers worn on different parts of the body in PAH. We had patients with PAH simultaneously wear two different accelerometers, compared measures between the two devices, and correlated the measures with standard clinical metrics in PAH. Methods and results: This was a single-centre, prospective observational study. Daily physical activity and daily total steps were measured using Actigraph GT9X Link and MC10 Biostamp nPoint for 5–10 days. Actigraph was worn on the non-dominant hand and the MC10 Biostamp nPoint was worn on the chest and leg with disposable adhesives. Twenty-two participants wore both accelerometers >12 h/day for an average 7.8 days. The average activity time measured by Actigraph was significantly higher than that measured by MC10 (251 ± 25 min vs. 113 ± 18 min, P = 0.0001). Actigraph's algorithm reported more time in light activity than moderate (190 ± 62 min vs. 60 ± 56 min, P = 0.0001). REVEAL 2.0 scores correlated highly with activity time measured using either device. Invasively measured haemodynamics within 7 days did not correlate with activity time or daily steps. Conclusion: Different activity trackers yield discordant results in PAH patients. Further studies are needed in determining the best device, optimal wear time, and different thresholds for activities in chronic diseases. Graphical abstract: